ANALISIS PENGELOLAAN KEUANGAN DESA PADA KANTOR WALI NAGARI TIKU V JORONG KECAMATAN TANJUNG MUTIARAKABUPATEN AGAM - Rahma Sucia; Ilham Illahi (CV. Adiba Aisha Amira, 2023)
This study aims to analyze Village Financial Management at the Wali Nagari Tiku V Jorong Office, Tanjung Mutiara District, Agam Regency, whether it is running well in accordance with Agam Regent Regulation Number 50 of 2018 concerning nagari financial management.This study used a qualitative method with an interview approach to the office apparatus of Walinagari Tiku V Jorong. By collecting data using the method of observation, interviews and documentation with the data used, namely Primary Data.The results of this study indicate that overall village financial management at the Walinagari Tiku V Jorong office has aspects which include planning, implementation, administration, reporting and accountability. In managing village finances carried out by the nagari government, it must comply with the provisions of the Agam Regent Regulation Number 50 of 2018. Financial management has been going well, marked by the increase in APBNagari funds received by Nagari Tiku v Jorong every year, and also increased community development and empowerment. However, there are also problems that occur in village financial management, namely there are funds from several sectors that are not realized at all and some are not realized up to 50% of the total budget. Village financial management at the Walinagari Tiku V Jorong office must be in accordance with the principles of transparency,accountability, participation, order and budget discipline with a very high level of effectiveness so that the policies set are sufficient and provide benefits to the community.